Access to communication technology for children with cerebral palsy. Issue 10 (October 2017) - Griffiths, Tom; Addison, Anne
Abstract: Children with a diagnosis of cerebral palsy (CP) may experience difficulties in producing clear speech and may benefit from the use of augmentative and alternative communication (AAC) systems. Such systems may include the use of high-tech hardware and software to allow the selection of words or symbols, to be transmitted to a communication partner through digital or synthesised voice. Children whose movement disorders are more severe may experience difficulties using standard human interface devices such as a mouse and keyboard and may require modified or specialised solutions to access and control their AAC systems. This review discusses contemporary definitions of access and outlines considerations for assessment and selection of such systems. The International Classification of Functioning, Disability and Health (ICF) is suggested as a helpful framework for decision-making. Given the complex presentation of many children with CP, a multi-disciplinary approach is emphasised.